2004
DOI: 10.1159/000075538
|View full text |Cite
|
Sign up to set email alerts
|

Persistent Psychological Distress in Patients Treated for Endocrine Disease

Abstract: Background: The purpose of the study was to assess the frequency and characteristics of psychological distress, even after adequate treatment, in the heterogeneous population of an endocrine outpatient clinic. Methods: 146 endocrine patients (31 males/115 females; age 39.4 ± 12.5 years), who were cured or in remission, were studied in a university endocrine outpatient clinic. Semistructured clinical interviews to assess psychiatric (Structured Clinical Interview for DSM-IV) and psychological (Diagnostic Criter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

10
59
0
2

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 83 publications
(71 citation statements)
references
References 17 publications
10
59
0
2
Order By: Relevance
“…On the other hand, in our data set, correlations between the degree of physical symptoms or endocrine disturbances and psychological distress and/or impairment of well-being were weak. Psychological distress appears to be common in many endocrine disorders (48,49). However, in any one individual, it may not be possible to predict the degree of psychological distress based on the presence or absence of individual symptoms or a specific symptom constellation alone.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, in our data set, correlations between the degree of physical symptoms or endocrine disturbances and psychological distress and/or impairment of well-being were weak. Psychological distress appears to be common in many endocrine disorders (48,49). However, in any one individual, it may not be possible to predict the degree of psychological distress based on the presence or absence of individual symptoms or a specific symptom constellation alone.…”
Section: Discussionmentioning
confidence: 99%
“…17,19,24,25 Sonino and colleagues showed that anxiety disorders in PCOS patients are common and that noticeable impairment of mental function may occur in these patients. 26 These women are at an increased risk of psychological ill health which may markedly reduce their quality of life. [18][19][20][21][22]27,28 Why these women are vulnerable to psychiatric disorders remains unclear; the contributing mechanisms for psychological disorders have not been completely understood, but they likely involve several pathways.…”
Section: Copyright © 2015 By Tabriz University Of Medical Sciencesmentioning
confidence: 99%
“…The application of the DCPR operational criteria has permitted to document the occurrence of demoralization across different medical settings, substantiating previous findings that used dimensional tools 20, 21 . In studies utilizing the DCPR, demoralization was found in 14-44% of patients with cardiac 22 , oncological 23 , dermatological 24 , gastrointestinal 25 and endocrine conditions [26][27][28] , in those recruited in primary care 29 and in consultation-liaison psychiatry settings 30,31 . Table 1 DCPR criteria for demoralization A through C are required A.…”
Section: Introductionmentioning
confidence: 99%